The Impact of Using the Trainings of Mental Visualization on Learning Crawl Swimming - Oun Adel Ghazi Al-Habashneh; Mqdad Al-Tarawneh; Omar Jamel Al-Jafreh (Deanship of Scientific Research (DSR), the University of Jordan, 2024)
Objectives: The study aimed to investigate the impact of using mental imagery exercises in teaching crawl swimming. Methods: The experimental approach was adopted for its suitability to the nature of the study. The study sample consisted of 30 male students enrolled in the swimming course (1) for the second semester of the academic year 2020-2021 at the College of Sports Sciences, Mu'tah University. They were purposefully selected and randomly assigned to two equally matched groups. The experimental group, comprising 15 students, utilized a proposed educational program accompanied by mental imagery exercises, while the control group, also consisting of 15 students, followed a standard educational program. The implementation of the educational program lasted for 8 weeks, with two instructional sessions per week and a total of 16 instructional units. Results: There were statistically significant differences at a significance level (≥ α 0.05) in teaching crawl swimming between the two groups in dimensional measurement, in favor of the experimental group, indicating the impact of using mental imagery exercises in teaching prone crawl swimming compared to the control group. The effect size ranged from 25.31% to 15.77%. The results also showed no statistically significant differences at a significant level (≥ α 0.05) between the two groups according to the "arm movements" test. Conclusions: It is recommended to incorporate mental imagery exercises into the instructional program for teaching the front crawl swimming technique, as they have a positive impact on improving and expediting the learning process. The use of mental visualization exercises for motor skills requiring more precise motor coordination and conducting studies and scientific research on different types of swimming and more complex skills, is recommended.